Densification behavior of yttria-stabilized zirconia powders for solid oxide fuel cell electrolytes - Dhruba Panthi; Nader Hedayat; Yanhai Du (Journal of Advanced Ceramics, 2018)
Abstract Yttria-stabilized zirconia (YSZ) is the most common electrolyte material for solid oxide fuel cells. Herein, we conducted a comparative study on the densification behavior of three different kinds of commercial 8 mol% YSZ powders: (i) TZ-8Y (Tosoh, Japan), (ii) MELox 8Y (MEL Chemicals, UK), and (iii) YSZ-HT (Huatsing Power, China). The comparison was made on both the self-supporting pellets and thin-film electrolytes coated onto a NiO–YSZ anode support. For the pellets, MELox 8Y showed the highest densification at lower sintering temperatures with 93% and 96% of the theoretical density at 1250 and 1300 °C, respectively. Although YSZ-HT showed a higher sintering rate than TZ-8Y, a sintering temperature of 1350 °C was required for both the powders to reach 95% of the theoretical density. For the thin-film electrolytes, on the other hand, YSZ-HT showed the highest sintering rate with a dense microstructure at a co-sintering temperature of 1250 °C. Our results indicate that besides the average particle size, other factors such as particle size distribution and post-processing play a significant role in determining the sintering rate and densification behavior of the YSZ powders. Additionally, a close match in the sintering shrinkage of the electrolyte and anode support is important for facilitating the densification of the thin-film electrolytes.